Les expressions urbaines d’une mobilisation contestataire : Cas du Hirak à Constantine - Nassima Baziz (Cybergeo, 2021)
On February 22nd, 2019, Algeria witnessed the mobilisation of hundreds of thousands of people, in cities around the country, to demand political change at the head of the state. More than a year after the Hirak uprising, this article, supported by a socio-urban study, questions how the Hirak manifests itself, expresses itself and spatializes itself in the city of Constantine and its public spaces. This research, which lasted almost a year, is based on a process of observations, sometimes floating, sometimes participating, in the weekly Friday marches, a series of interviews with protestors and activists, as well as the urban analysis of the route followed. It highlights the attitudes of negotiation and/or resistance that are expressed through a particular appropriation of public spaces, considered here in their physical, social and political dimensions. Attitudes that lead to the emergence of singular appropriations in Constantine, such as the emergence of buffer zones along the route, urban performance sites and symbolic sites that have become emblems of the protests.